DNA methyltransferase inhibition promotes recruitment of myeloid-derived suppressor cells to the tumor microenvironment through induction of tumor cell-intrinsic interleukin-1. (1st January 2023) - Traynor, Sofie; Terp, Mikkel Green; Nielsen, Aaraby Yoheswaran; Guldberg, Per; Jakobsen, Mie; Pedersen, Pernille Gejl; Gammelgaard, Odd Lilleng; Pedersen, Christina Bøg; Pedersen, Mathilde Thybo; Rattenborg, Sofie; Ditzel, Henrik Jørn; Gjerstorff, Morten Frier
Abstract: DNA methyltransferase (DNMT) inhibitors are used for treatment of certain hematological malignancies and exert anti-cancer activity through diverse mechanisms, including reexpression of tumor suppressor genes and anti-viral responses triggered by expression of endogenous retroviruses. Despite advances in the pharmacokinetic properties of DNMT inhibitors, the efficacy of these drugs in solid cancers remains low. Here, we show in cell lines and clinical and experimental tumors across multiple cancer types that DNMT inhibition induces the expression of interleukin-1 (IL-1), a cytokine with proinflammatory and protumorigenic properties. Specifically, this tumor-intrinsic IL-1 expression modulates the chemokine landscape of tumors and leads to the recruitment of monocytic myeloid-derived suppressor cells to the tumor microenvironment, processes that can be blocked by IL-1 antagonists. Molecular analysis demonstrates complex patterns of IL-1 and interferon activation and crosstalk in response to DNMT inhibition, which depend on the integrity of IRF- and NF-κB-mediated antiviral pathways and may determine the outcome of DNMT-inhibitor treatment. Together, our results show that DNMT inhibitors may negatively affect the microenvironment of a large subset of tumors and suggest that co-treatment with IL-1 antagonists may be a favorable combination for these patients. Highlights: DNA methyltransferase inhibition induces IL-1-mediated antiviral responses in tumors across multiple cancer types. DNA methyltransferase inhibition-mediated IL-1 expression drives recruitment of myeloid-derived suppressor cells to tumor. There are complex patterns of IL-1 and IFN activation and crosstalk in response to DNA methyltransferase inhibition in tumors. Co-treatment with DNMT inhibitors and IL-1 antagonists may be a favorable combination for some patients with solid tumors.